High resolution hard X-ray 3D mapping of a Macaca fascicularis eye: A feasibility study without contrast agents. (July 2018) - Mittone, A.; Ivanishko, Y.; Kovalev, S.; Lisutina, P.; Lotoshnikov, M.; Tkachev, S.; Tkacheva, M.; Crippa, L.; Dmitriev, V.; Bravin, A.
Highlights: First 3D model of Macaca fascicularis eye realized at 3 µm 3 voxel size. The CT images have been obtained without the use of contrast agents. High image contrast has been achieved using X-ray phase-contrast CT imaging. The imaging results have been validated by histology workup. Preliminary trials of high dose reduction (∼40 times) are presented. Abstract: Several complementary methods able to visualize the internal structures of eyes are used in the clinical practice in the diagnosis of pathologies affecting a specific zone of the eye. Despite the significant technological progress, the visualization of the entire eyeball at micrometric resolution is yet an unsolved task both in clinical diagnostics and in laboratory research. With this respect, high resolution 3D images of the eyeball would be extremely useful, in the study of various pathologies of the retina, the lens, and of the optic nerve. In this work we combined the state-of-the-art of micro computed tomography technology with phase-contrast imaging, a recent highly sensitive technique well adapted to investigate soft tissues without the use of contrast agents; we applied the technique in the post-mortem analysis of monkey eyes, which share several similitudes with the human organ. We reported here vascular, nervous and anatomical details of monkey eyes imaged with a 3.1 × 3.1 × 3.1 µm 3 voxel size as well as the first 3D visualisation of the entire globe of Macaca's fascicularis eye. Results have also been compared with, and validated by, histological analysis.